Selective Muscular Electrostimulation with exponential currents in the functional recovery of patients with Bell's Palsy (Journal on studies and research of academic knowledge, 2022)
Peripheral facial paralysis affects facial function, its recovery is one of the challenges of physiotherapy, electrostimulation is currently a controversial therapeutic resource. Therefore, this research arises with the objective of analyzing the parameters of electrostimulation with exponential current, necessary to achieve functional recovery in patients with Bell's palsy included in a quasi-experimental study of the Kinesiology University Service from 2017 to 2019, framed In a quasi-experimental, prospective, longitudinal design, patients with Bell's palsy were included, who were evaluated according to the House Brackman scale and treated using a protocol of selective muscle electrostimulation with unidirectional exponential currents. Of 30 patients treated, a mean age of 40 years was observed. Considering the electrostimulation parameters, it was found that the denervated facial muscles responded with variable intensities at the beginning and end of the treatment and the average value of the initial pulse width was 262.3 milliseconds and 68.6 milliseconds at the end of the treatment. On the other hand, the average value of functional recovery according to House Brackman was: 3.43 at the beginning and 1.53 at the end of treatment. Regarding time, 15 sessions on average was the time required to demonstrate said improvement in facial function. In conclusion, the use of exponential current in patients with Bell's palsy is a therapeutic resource that helps in the functional recovery of the affected muscles,
Keywords: Peripheral facial paralysis; Electrotherapy; Physiotherapy; Electrostimulation